Comparing outcomes after open and endovascular chronic mesenteric ischemia revascularization –10-year single-center experience - Helena Fidalgo; Tiago Ribeiro; Fábio Pais; Joana Cardoso; Carolina Tavares; Ricardo Correia; Daniela Gonçalves; Maria Emília Ferreira (Angiologia e Cirurgia Vascular)
INTRODUCTION: Chronic mesenteric ischemia (CMI) is a rare but life-threatening disease. This study aimed to analyze the safety and effectiveness of open (OR) and endovascular (ER) revascularization and respective outcomes in a consecutive series of CMI patients.